The role of collagen-containing agents in the prevention and treatment of osteoarthritis: resolution of the expert council - A. M. Lila; O. N. Tkacheva; B. A. Polyaev; L. I. Alexeeva; E. A. Taskina; A. V. Naumov; Yu. V. Kotovskaya; V. V. Arykov; I. G. Kozlov; I. V. Kukes; S. A. Parastaev (Современная ревматология)
This publication presents expert recommendations based on an objective analysis of results from evidence-based studies, systematic reviews, and meta-analyses, as well as on the authors' own clinical experience in using a new category of collagen-containing agents for the prevention and treatment of osteoarthritis.